The German pediatric integrated care survey (PICS-D): Translation, adaptation, and psychometric testing - Willems, Jana; Bablok, Isabella; Sehlbrede, Matthias; Farin-Glattacker, Erik; Langer, Thorsten (Frontiers in Pediatrics, 2022)
Background Integrated care models aim to strengthen the collaboration between healthcare sectors to ensure a higher quality of care for children with chronic conditions. Assessing pediatric healthcare integration through families' experiences, therefore, is essential. Our study aimed to psychometrically test the PICS-D, the first German-language integrated care questionnaire, which is based on the Pediatric Integrated Care Survey (PICS) developed in the USA. Methods We examined construct validity using exploratory and confirmatory factor analyses (structural validity). Cronbach's α and McDonald's ωt coefficients explored reliability. Cognitive interviews assessed wording comprehension and item appropriateness. Results PICS-D was completed by 204 caregivers of children with chronic conditions (women = 84%; mean age = 41.4 years). Factor analyses identified 3 factors: “Team quality & communication”, “Family impact”, and “Access to care”. The 3-factorial structure showed a satisfying fit to confirmatory classical-test-theory-based models. Due to the insufficient reliability of the third factor, we recommend using only factors 1 and 2 for scoring the PICS-D. Conclusion The PICS-D is a 13-item questionnaire to assess family-reported experiences in pediatric care integration, which has good psychometric properties. It may be useful in guiding quality improvement efforts or measuring the impact of a care plan or care model. Trial registration: German Clinical Trials Register (DRKS): DRKS00018778; Trial registration date 05. December 2019—Retrospectively registered; https://apps.who.int/trialsearch/Trial2.aspx?TrialID=DRKS00018778.